Mesophotic.org: a repository for scientific information on mesophotic ecosystems. (14th December 2019) - Bongaerts, Pim; Perez-Rosales, Gonzalo; Radice, Veronica Z; Eyal, Gal; Gori, Andrea; Gress, Erika; Hammerman, Nicholas M; Hernandez-Agreda, Alejandra; Laverick, Jack; Muir, Paul; Pinheiro, Hudson; Pyle, Richard L; et al.
Abstract: Mesophotic coral ecosystems (MCEs) and temperate mesophotic ecosystems (TMEs) occur at depths of roughly 30–150 m depth and are characterized by the presence of photosynthetic organisms despite reduced light availability. Exploration of these ecosystems dates back several decades, but our knowledge remained extremely limited until about a decade ago, when a renewed interest resulted in the establishment of a rapidly growing research community. Here, we present the 'mesophotic.org ' database, a comprehensive and curated repository of scientific literature on mesophotic ecosystems. Through both manually curated and automatically extracted metadata, the repository facilitates rapid retrieval of available information about particular topics (e.g. taxa or geographic regions), exploration of spatial/temporal trends in research and identification of knowledge gaps. The repository can be queried to comprehensively obtain available data to address large-scale questions and guide future research directions. Overall, the 'mesophotic.org ' repository provides an independent and open-source platform for the ever-growing research community working on MCEs and TMEs to collate and expedite our understanding of the occurrence, composition and functioning of these ecosystems. Database URL: http://mesophotic.org/